Pengembangan Bahan Ajar Berbasis Masalah Pada Materi Struktur Dan Fungsi Tumbuhan Kelas VIII Mata Pelajaran IPA di MTs MA Pasirdurung - Badri Wijaya; Sholeh Hidayat; Fadlullah Fadlullah (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2021)
This development research aims to describe the process of developing teaching materials and produce appropriate problem-based teaching materials for class VIII MTs students. This development procedure refers to the ADDIE research and development model. The development of problem-based teaching materials is carried out in 5 stages, the subject of the trial is class VIII MTs MA Pasirdurung, which consists of an initial field trial of 4 students, a field trial of 8 students, a field trial of 20 students. Techniques and data collection using interviews, observations, and questionnaires. Data were analyzed using quantitative descriptive methods. In this study, the final product was obtained in the form of problem-based teaching materials that were feasible to use. This is evidenced by the results of the product assessment by material experts which are stated to be very good (4.50), the results of product assessments by media experts are stated to be good (3.72). The results of the initial field trials were declared feasible (0.89), the results of the field trials were declared feasible (0.96) and the results of the field trials were declared feasible (0.98) and student learning activities were quite active (3.90) and the results student learning increased by an average (77.5)